2010
DOI: 10.5352/jls.2010.20.12.1812
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Breakfast Size to Metabolic Risk Factors

Abstract: Skipping breakfast is a risk factor closely related to metabolic syndrome and obesity. We analyzed the relationship between breakfast size, metabolic syndrome and obesity. The study included 5,548 adults who visited a health promotion center at Pusan National University from January to November of 2006. Subjects were divided into four groups according to breakfast size -skipper group (no breakfast), small intake group, medium intake group and large intake group. 959 (17.3%) of the 5548 subjects were included i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Several studies that analyzed breakfast and metabolic risks have suggested that skipping breakfast increases total cholesterol and LDL cholesterol, reduces postprandial insulin sensitivity [ 22 ], and increases blood pressure [ 19 ]. However, in another study of those who regularly ate breakfast, the triglycerides, fasting blood glucose, systolic and diastolic blood pressure were significantly high in the regular breakfast groups (more than 300 kcal for breakfast), and HDL cholesterol was low [ 23 ]. In the regular breakfast group, carbohydrate intake was found to be higher than in the skipping breakfast group, and triglyceride level, a risk factor for metabolic syndrome, was significantly higher [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies that analyzed breakfast and metabolic risks have suggested that skipping breakfast increases total cholesterol and LDL cholesterol, reduces postprandial insulin sensitivity [ 22 ], and increases blood pressure [ 19 ]. However, in another study of those who regularly ate breakfast, the triglycerides, fasting blood glucose, systolic and diastolic blood pressure were significantly high in the regular breakfast groups (more than 300 kcal for breakfast), and HDL cholesterol was low [ 23 ]. In the regular breakfast group, carbohydrate intake was found to be higher than in the skipping breakfast group, and triglyceride level, a risk factor for metabolic syndrome, was significantly higher [ 24 ].…”
Section: Discussionmentioning
confidence: 99%